A study on the possibility of high performance computation using quantum tunnelling photons. (13th February 2006) - Musha, Takaaki
It is widely believed that microprocessor performance will fail to hold in the next decade owing to the brick wall arising from the fundamental physical limitations of the computational process. Instead of conventional processors, the quantum processor is considered to have the possibility to overcome these limitations. However, the influence of the energy cost due to the uncertainty principle, which may prevent speeding up the quantum computation, was not considered. On the basis of the theorem that the evanescent photon is a superluminal particle, the possibility of a high performance computer system compared with conventional silicon processors has been studied. From the theoretical analysis, it is shown that computational energy loss, which utilises tunnelling photons, is much lower than in conventional silicon processors.